2016
DOI: 10.1002/jhet.2729
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Imino Containing Tetrahydrochromeno[2,3‐d]pyrimidines

Abstract: Some new derivatives of 3,5‐diaryl‐4‐imino‐5,7,8,9‐tetrahydro‐3H‐chromeno[2,3‐d]pyrimidine have been prepared through a condensation reaction of 2‐amino‐4‐aryl‐3‐cyano‐5,6,7,8‐tetrahydrobenzo[b]pyrans with triethyl orthoformate in boiling acetic anhydride followed by cyclization with primary aryl amines in the presence of a few drops triethylamine as catalyst in refluxing ethanol. The products were characterized on the basis of IR, 1H‐NMR, and 13C‐NMR spectral and microanalytical data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Taking all these facts into consideration, and in conjunction with our earlier studies of synthesis of heterocyclic compounds , herein, we report the synthesis of some new derivatives of 6‐alkylamino‐1,3‐diphenyl‐1 H ‐pyrazolo[3,4‐ b ]pyridine‐5‐carbonitrile 4a–f in synthetically useful yields by Knoevenagel condensation of 5‐chloro‐1,3‐diphenyl‐1 H ‐pyrazole‐4‐carbaldehyde 1 with malononitrile 2 in ethanol containing a few drops of glacial acetic acid at reflux temperature, which afforded compound 3 , followed by cyclization with primary alkyl amines in the presence of 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) as catalyst in refluxing ethanol (Scheme ). To the authors' knowledge, compounds 4a–f are new and have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 89%
“…Taking all these facts into consideration, and in conjunction with our earlier studies of synthesis of heterocyclic compounds , herein, we report the synthesis of some new derivatives of 6‐alkylamino‐1,3‐diphenyl‐1 H ‐pyrazolo[3,4‐ b ]pyridine‐5‐carbonitrile 4a–f in synthetically useful yields by Knoevenagel condensation of 5‐chloro‐1,3‐diphenyl‐1 H ‐pyrazole‐4‐carbaldehyde 1 with malononitrile 2 in ethanol containing a few drops of glacial acetic acid at reflux temperature, which afforded compound 3 , followed by cyclization with primary alkyl amines in the presence of 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) as catalyst in refluxing ethanol (Scheme ). To the authors' knowledge, compounds 4a–f are new and have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 89%
“…197 There are some reports [198][199][200] in the literature on the synthetic drives of such biologically promising heterocyclic scaffolds. Davoodina and co-workers 201…”
Section: Review Syn Thesismentioning
confidence: 99%
“…They are oen synthesized by multicomponent reactions which enable the desired products to be isolated in a few steps via a single-pot operation. [14][15][16][17][18][19][20] Chromenopyrimidine derivatives have been reported to be light emitters which can be ne-tuned by varying the substituents on the chromenopyrimidine core. 14 This the class compounds as potential emitters in optoelectronic devices such as organic light-emitting diodes (OLEDs).…”
Section: Introductionmentioning
confidence: 99%